TYPES OF ORGANISMS DECOMPOSERS OF SOIL POLLUTANTS - Ika Karyaningsih (Journal of Forestry And Environment, 2018)
Pollutants will land declining soil quality and land productivity and lower the carrying capacity of land to humans and the environment. Various types of pollutants require certain types of soil organisms to decompose both microbes and soil fauna, so this paper focuses on identifying the types of decomposers in each pollutant. Soil microbes (bacteria) are more widely used for various types of pollutants while the soil fauna acts as a chunk of solid material which will then be broken down by microbes.